DIMENSIONS OF EDUCATION MANAGEMENT ( LAW AND PROFESSINAL) - Tri Aska Wijayanti; Suharno Suharno; Sri Yamtimah (Universitas Sebelas Maret, 2018)
This paper aims to describe research in primary schools and explain how the dimensions of legal and professional education management at SDN Bulukantil, Jebres, Surakarta. This research uses qualitative descriptive method with data collection through interview technique. In principle, there are four competencies, namely personality, managerial, entrepreneurship, supervision and social, while teachers have pedagogic, personality, social and professional competence. From two sources of interviews, it is explained that the legal and professional dimensions are well implemented in Bulukantil Primary School in Surakarta. The results of this study can be concluded that in the legal dimension of legal education management and professional headmasters and teachers at SDN Bulkatil has been fulfilled.